الصورة السينمائية في الفيلم الثوري الجزائري؛ من الجمالية إلى الإيديولوجيا " معركة الجزائر" « LA BATAILLE D’ALGER » نموذجا (Revue El-Wahat pour les Recherches et les Etudes, 2021)
This Study Seeks To Illustrate The Ideological Dimension Within Which The Film Director Of The Battle Of Algeria LA Bataille D'alger Jello Bentkowvo Gillo Pontecorvo In His Photographic Footage, Which Has Shown A Certain Historical Period In The History Of The Triumphant Algerian Revolution.    After Subjecting A Sample Of Images To Analysis And Objective Criticism, Based On The Progress Of The Philosopher And French Artist Laurent Jarvforo LAURENT Erau "Regarding The Analysis Of The Photograph, The Three Elements Are Passable: 1 Description/Descriptions 2 Context Study/L'etude Du Context 3 Exegesis/ L'interpration That We Have The Historical Film Tried To Promote The Policy Of French Sabotage In Algeria Then More Than He Tried To Praise The Algerian Revolution As Planned By Most Algerian Viewers.   Keywords: Ideology; Image; Cinema; Model Publisiter; Algerian Revolution